The Middle Classes in the west Paris Periurban Fringes - Claire Aragau; Martine Berger; Lionel Rougé (Cybergeo, 2019)
Paris region is confronted to an important phenomenon of social polarization. Periurban rings surrounding the city are today the only metropolitan areas in which mid-management jobs are the most numerous among active socio-professional group, although their importance tends to decrease due to the strong growth and spread of executive jobs. The ubiquity of spatial distribution of the middle class hides however a great diversity of social positions, statuses, residential strategies within the category. According to the social milieu and the residential proximities but also the residential and daily mobility strategies, a fracture takes shape between a fraction of the middle class assimilated to executives belonging to a “high middle class”, and the “low middle class”. The latter being composed of foremen and supervisors, often assimilated to white-collars and laborers, often constrained to become owners further away from town. Statistical analysis based on detailed files from the census and households inquiries conducted in the Parisian great west (Grande Couronne and adjoining administrative departements) highlight the integration of the middle class in the periurban space, making it a space of resources, family proximities, social ascension and security through homeownership. Yet, these analyzes also highlight the weakening of a fraction of the middle class caused both by the rapid increase of property value in the closest suburbs and the increasing cost of mobility. While household adaptation strategies often favor proximities, local governments are seeking new forms of periurban development.